KINETIC CHARACTERIZATION OF BIOMETHANE MESOPHILIC AND THERMOPHILIC PRODUCTION FROM ANAEROBIC DIGESTION OF FILTER CAKE AND VINASSE - Loyo-Inclán, Carlos; Miranda-Medina, Anilú; Parra-Bartolo, Sheila Paulina; Barradas-Dermitz, Dulce María; Bravo-Figarola, Marisol; Hayward-Jones, Patricia Margaret (Centro Azúcar Journal, 2025)
Introduction: As part of the path toward a sugarcane biorefinery scheme, it is necessary to study the utilization of byproducts such as sugarcane filter cake and vinasse, particularly as energy sources through their anaerobic conversion to biomethane. Objective: To generate a kinetic characterization of this conversion. Materials and Methods: A sample from a slaughterhouse wastewater treatment plant was used as the inoculum and substrates were samples of vinasse and filter cake, cultured in mesophilic and thermophilic ranges, useful for scaling-up. Results and Discussion: Mesophilic conditions, with vinasse as a substrate, produced a higher amount of accumulated biomethane (1466.7 NmL) compared to the vinasse and filter cake mixture (832.8 NmL) using an I/S of 1 (g VS/g VS). Anaerobic digestion in the thermophilic range decreased biomethane production by 67.71% (vinasse) and 91.34% (filter cake-vinasse) under identical operating conditions. Biomethane production was reported at 90% on the second day. Conclusions: Under mesophilic conditions, biomethane production increased by an average of 79.52%. A higher Biomethane Potential (BMP) was achieved using only vinasse as a substrate. Of the ten kinetic models evaluated, the Hill equation is flexible for high and low biomethane production; however, it only generates one kinetic parameter. The Gompertz equation is recommended because it showed an R2 greater than 0.99 for high production and three kinetic parameters. The Avrami and modified Avrami equations are suitable for low biomethane production.